Influence of skills and knowledge on the financial attitude of university students - Loza, Renzi (2023)
The article analyzes the influence of knowledge and skills on the financial attitude of university students. Financial knowledge, skills, and attitudes are components of what is called financial literacy. The theory of human capital emphasizes the importance of  investing in human capital to enhance individuals' decision-making. The empirical analysis uses a sample of 531 university students from Tacna, Peru. The results of the proposed structural equation model corroborate that financial knowledge and skills directly and positively influence university students' financial attitude. The findings offer important implications for students and higher education institutions by highlighting the importance of incorporating courses and workshops on personal finance to acquire knowledge and improve students' financial skills and, consequently, facilitate the development of a financial attitude that allowsthem to make more informed financial decisions.